Prevalence and Associated Risk Factors of Dyspareunia and Incontinence Disorders in Postpartum Women: A Prospective Cross-Sectional Study (International Journal of Environmental Sciences, 2025)
Background:Postpartum health issues such as dyspareunia, urinary incontinence (UI), and bowel incontinence significantly impact maternal well-being but are frequently underreported and underdiagnosed. These conditions, influenced by obstetric factors and pelvic floor trauma, contribute to a decline in quality of life and intimate relationships.Objectives:To determine the prevalence and associated risk factors of dyspareunia, urinary incontinence, and bowel incontinence among postpartum women within six months of delivery.Methods:This was a prospective cross-sectional study conducted over three months at a tertiary care hospital. Ninety-six women aged 20–35 years, within six months postpartum, were enrolled using purposive sampling. Data collection included demographic details, obstetric history, and validated questionnaires such as the Pelvic Floor Distress Inventory (PFDI) and Female Sexual Function Index (FSFI). Data were analyzed using SPSS version 22, with p<0.05 considered significant.Results:Dyspareunia was reported by 34.4% of participants, UI by 28.1%, and bowel/flatus incontinence by 17.7%. Significant risk factors for dyspareunia included vaginal delivery (p=0.011) and perineal trauma (p=0.003). UI was significantly associated with higher BMI (p=0.035), vaginal delivery (p=0.012), and perineal trauma (p=0.019). Age, parity, and comorbidities showed no significant associations with these conditions.Conclusion:Postpartum pelvic floor disorders are prevalent and associated with specific obstetric risk factors. Systematic screening and early intervention are essential to improve long-term maternal health outcomes and promote quality postpartum care.